ANALISIS FAKTOR-FAKTOR YANG MENJADI PERTIMBANGAN NASABAH DALAM MENGGUNAKAN JASA BANK SYARIAH (Studi Empiris Pada Nasabah Bank Syariah Mandiri Cabang Purwokerto) - SE, Parno (STIE Muhammadiyah Pekalonga, 2012)
The research was conducted at Bank Syariah Mandiri Branch of Purwokerto. The research entitled âAnalysis of Factors Becoming Consideration in Using The Bank Syariah Mandiri Service (A Case Study on The Consumers of Bank Syariah Mandiri Branch of Purwokerto).This research aims at analyzing which factor most dominant for the customers in using the services offered by the Bank Syariah Mandiri Branch of Purwokerto and then to investigate whether there are relationship between each respondent characteristic with each factor becoming consideration in using the service of the Bank Syariah Mandiri. The population are consumers who save fund at the Bank Syariah Mandiri Branch of Purwokerto and the sample size consist of 90 respondent. The research employs simple random sampling technique. Data analytical method applies descriptive analysis, cross-tab ( X2), and factor analysis.Based on the empirical data analysis it can be concluded that factors which are dominant becoming consideration for the consumers in using the Bank Syariah Mandiri Branch of Purwokerto are those related to the attributes of the syariah consisting of the five factors: existence of prohibition to interest, sharing holder system which make more calm, Islamic law principle in every practice of banking transaction, investment/defrayal of the Bank Syariah Mandiri for the Islamic lawful business, and joint in transaction of syariah banking. Finally, it is proved that there are significant relation between the customers characteristic consisting of gender, age, status, education, and the product saving (Tabungan BSM, Tabungan Mabrur, Saving Deposit BSM, Giro BSM) with factors becoming consideration of the consumers in using the Bank Syariah Mandiri Branch of Purwokerto. Â Â Keywords: Syariah Bank, Consumer Behavior, Factor, Consideration